Islamic Republic of Mauritania : Request for an Extension of the Extended Credit Facility Arrangement-Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
The authorities have requested a three-month extension of the Extended Credit Facility (ECF) arrangement set to expire on December 5, 2020. The three-year arrangement was approved by the Executive Board on December 6, 2017 with access of SDR 115.92 million (90 percent of quota); additional access of SDR 20.24 million (about 15.7 percent of quota) was approved on September 2, 2020. On April 23, 2020, the Board also approved the disbursement of SDR 95.68 million (about 74.3 percent of quota) under the Rapid Credit Facility to address urgent balance of payment needs due to the COVID-19 pandemic.